Pancasila sebagai Pokok Pangkal Sudut Pandang Bagi Ilmu Menurut Notonagoro - Mudhofir, Ali (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2006)
According to Notonagoro, everything came from matter and spirit. All phenomena in the universe have material and final cause.Everything, including sciences, has deity background. Sciencesbase on reason, willing, intuition, inspiration, and revelation. Bothspeculative and empirical thought with their variation base on thecausal law, in order to take their useful for human life, withoutdepend the truth and reality on usefulness for life. In scientificdeveloping, Pancasila, therefore, is a guideline for sciencesâ€”humanities, social and natural sciences. Research and sciencesdeveloping in Indonesia ought to be based on and spirited byPancasila. It is very important for national education generally andspecially for high education according to the guideline of 1945National Constitution. As a basis of scientific point of view,Pancasila allow for scientists do not to adopt the position ofscience for the sake of science; but teleological, namely, theyought to priority the sciences for good life. Moreover, they oughtto care of the direct and pure task of sciences, namely, in order toget truth and reality.Â